2007
DOI: 10.1038/sj.bmt.1705690
|View full text |Cite
|
Sign up to set email alerts
|

Blood stream infection after hematopoietic stem cell transplantation is associated with increased mortality

Abstract: Blood stream infection (BSI) is a serious complication of hematopoietic stem cell transplantation (HSCT). The aim of this retrospective cohort analysis was to describe BSI after HSCT, and to assess the predictors and outcomes of BSI after HSCT using multivariable modeling. Of the 243 subjects transplanted, 56% received allogeneic HSCT and 106 (43.6%) developed BSI. Of the 185 isolates, 68% were Gram-positive cocci, 21% were Gram-negative bacilli (GNR) and 11% were fungi. Type of allogeneic HSCT was an independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
152
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(175 citation statements)
references
References 39 publications
18
152
4
1
Order By: Relevance
“…27 Gram-positive organisms, especially CNS, were the most frequent etiology of BSI in both periods, in agreement with other studies involving HSCT recipients. 3,5,10,28 The frequency of Gram negatives was similar in both groups, as was the rate of multidrug resistance among them. The overall rate of multidrug-resistant Gram-negative bacilli was 21%.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…27 Gram-positive organisms, especially CNS, were the most frequent etiology of BSI in both periods, in agreement with other studies involving HSCT recipients. 3,5,10,28 The frequency of Gram negatives was similar in both groups, as was the rate of multidrug resistance among them. The overall rate of multidrug-resistant Gram-negative bacilli was 21%.…”
Section: Discussionmentioning
confidence: 77%
“…This finding is in line with other studies that have found a higher risk of BSI in this specific group of transplant recipients. 3,7 During the pre-engraftment period, we identified the presence of neutropenia, a central venous catheter and severe mucositis as important risk factors for BSI. During the pre-engraftment phase it is likely that mucosal damage allows bacteria to enter the bloodstream and the lack of neutrophils hampers their effective clearance, thus leading to BSI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations